Deformation-dependent peak floor acceleration for the performance-based design of nonstructural elements attached to R/C structures. Issue 2 (May 2021) - Muho, Edmond V; Pian, Chao; Qian, Jiang; Shadabfar, Mahdi; Beskos, Dimitri E
This study introduces a simple and efficient method to determine the peak floor acceleration (PFA) at different performance levels for three types of plane reinforced concrete (RC) structures: moment-resisting frames (MRFs), infilled–moment-resisting frames (I-MRFs), and wall-frame dual systems (WFDSs). By associating the structural maximum PFA response with the deformation response, the acceleration-sensitive nonstructural components, and the building contents, can be designed to adhere to the performance-based seismic design of the supporting structure. Thus, the proposed method can accompany displacement-based seismic design methods to design acceleration-sensitive nonstructural elements to comply with the deformation target of the supporting structure. The PFA response shape is represented by line segments defined by key points corresponding to certain floor levels. These key points are defined by explicit empirical expressions developed herein. The maximum PFA response is correlated with the maximum interstory drift ratio (IDR) and other vital characteristics of the supporting structure such as the fundamental period. The proposed expressions are established based on extensive nonlinear dynamic analyses of 19 MRFs, 19 WFDSs, and 19 I-MRFs under 100 far-fault ground motions scaled to capture different deformation targets. Realistic examples demonstrate the efficiency of the proposed method to assess the PFA response at a given IDR, making the method suitable in the framework of performance-based design.